Purchasing practices for selected fresh produce in deluxe hotels and full service restaurants in Metro Manila - Parker, Lea Buenaventura; Catral, Ma. Lourdes D. (2007., 2007)
This descriptive research is aimed at studying current purchasing practices and specifications for fresh produce (fruits and vegetables) required by the food and beverage departments of hotel;s and restaurants in Metro Manila. Deluxe hotels accredited by the Department of Tourism in the Philippines and full-service restaurants listed in the Hotel and Restaurant Association of the Philippines was the sampled population. Descriptive statistics, notably the standard error of means and comparison of means between hotels versus restaurants were utilized. Illustrations of projected volume quantity requirements of fresh produce purchased by establishments were added information. Purchasing procedures in the hotels and restaurants were quite comparable. The decision for purchasing types, quality and quantity of fresh produce was the chef's responsibility while purchasing was that of the purchasing manager. Hotels followed the formal bidding method while restaurants practiced single source purchasing. Detailed purchasing procedures were obtained to form part of the baseline information that could benefit the concerned sectors. The types of fresh produce ordered regularly by the establishments in the largest quantities were: pineapple, mango, melon, bananas, apples and oranges. Vegetable requirements were potatoes, carrots, tomatoes, lettuce and onions. Quality requirements were based on written descriptions of fruits and vegetables and could be used in establishing formal specification standards. Establishments gave primordial value to quality, evident in their most important criteria for selecting suppliers, "consistent quality of the product" and the suppliers' "reliability" on this. They also cited "inconsistent quality" as the main problem and resorted to purchasing the higher quality imported produce, despite high costs. This study contributed practical but valuable information in at least one market of users of fresh produce. Recommendations dealt with ways that could assist both hotels and restaurants, including the supply chain in the standardization and improvement of its products and services.
Thesis (M. Food Service Administration)--University of the Philippines Diliman
Keywords: Hospitality industry -- Purchasing. -- Philippines -- Metro Manila; Food service industry -- Purchasing. -- Philippines -- Metro Manila